Practicing IELTS Writing for L2 Writers with ChatGPT; An Exploratory Self-Study - Dwi Budidarma Sutrisno (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2023)
The emergence of Generative Artificial Intelligence especially ChatGPT recently as the new technology has invited many differing opinions towards both learner and educators of English. Even though ChatGPT has the main purpose to assist the users’ working based on the given prompt to be generated, however, as a tool it can be also considered to belong within the realm of computer-assisted language learning considering several studies have been looking for an intersection between ChatGPT with CALL. For example, ChatGPT exploration especially with Japanese students' context (Sakai, 2023). Moreover, despite the many studies looking at how ChatGPT can be integrated to help with grammatical error correction related topics (Fang et al, 2023) or connecting ChatGPT with Grammarly (Wu et al, 2023). However, not many studies have attempted to explore ChatGPT to help L2 writers practicing IELTS (International English Language Testing System) Writing as a crucial language score requirement to study abroad. Therefore, This study aims to investigate (1) How ChatGPT generates answers towards understanding IELTS Writing Task? (2) How ChatGPT can help L2 writers practicing IELTS Writing? and (3) What are my reflections as the researcher exploring ChatGPT for practicing IELTS Writing? This study uses methodology of self-study inspired by Grant Cooper (2023) in order to conduct this exploratory self-study research. It can be concluded that ChatGPT can be an alternative for L2 writers practicing IELTS Writing section Part 2 by utilizing ChatGPT to generate writing prompts then generate feedback of the writing based on the prompt. The feedback includes structure and organization, development of ideas, vocabulary and word choices, grammar and sentence structure, as well as conclusion. ChatGPT can also provide estimated scores for the IELTS writing practice for each component including task response, coherence and cohesion, lexical resource, grammatical range and accuracy then overall band.